Islam dan Pluralisme: Studi Peran Fungsionaris Adat Masyarakat Tengger - Naibin, Naibin (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Historically, the Tengger community is known as a tribal society that maintained the religion of their ancestors as a singular belief system. It was only after the post-Reformation era in 1998 that Hinduism and Islam became the predominant religions adopted by the Tengger people. More than 25 years after the Reformation, amid religious conflicts across several regions of Indonesia, the Tengger community continues to prioritize harmony within a framework of pluralism and tolerance. This study examines the relationships among Islam, Hinduism, and Tengger custom to understand how the Tengger people maintain social harmony and identify the dominant factors that shape and sustain harmony within a plural society. The research employed a field-based approach, conducted directly within the natural context of the subjects, to obtain empirical data relevant to real-world phenomena. This approach enables an in-depth analysis of behaviors, conditions, and social interactions. The results of this study indicate a collaborative relationship among Islam, Hinduism, and local cultural practices, in which both religions complement each other without abandoning substantive elements. Harmony is maintained through customary ceremonies in which adherents of all religions participate collectively to preserve traditional rituals. The dominant role in sustaining social harmony within the Tengger community is held by adat functionaries (adat judges, adat chiefs, and Wali Tanah), whose authority is directly recognized by the community, making their decisions binding and respected by the Tengger people.